PENGARUH KOMPETENSI DAN KEPEMIMPINAN TERHADAP MOTIVASI SERTA DAMPAKNYA PRODUKTIVITAS PEGAWAI PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN OGAN ILIR - Herman (Politeknik Ubaya, 2025)
Abstrak (Abstract) This study aims to determine and prove the Influence of Competence and Leadership on Motivation and Its Impact on Employee Productivity at the Public Works and Spatial Planning Office of Ogan Ilir Regency, both directly and indirectly, the population of this study was all Employees at the Public Works and Spatial Planning Office of Ogan Ilir Regency, totaling 61 Employees as research samples. Data analysis used through the PLS program. The results of this study indicate that Competence has a significant effect on motivation, Leadership has a significant effect on Motivation. Competence does not have a significant effect on Productivity, Leadership does not have a significant effect on Employee Productivity at the Public Works and Spatial Planning Office of Ogan Ilir Regency and Motivation has a significant effect on Employee Productivity at the Public Works and Spatial Planning Office of Ogan Ilir Regency. The R-Square value of the Motivation variable is 0.895, meaning that the Motivation variable can be explained by the Motivation variable (Y) by 89.50% while the remaining 10.50% is explained by other variables. For the R-Square value of Productivity (Z) of 0.998, meaning that the Productivity variable (Z) can be explained by the competency variables (X1) and Leadership (X2) by 99.80% while the remaining 06.00% is explained by other variables. Keywords: Competence, Leadership, Motivation and Productivity